Profil Kesulitan Belajar Siswa Kelas XI Putra pada Berbagai Submateri Laju Reaksi di Lingkungan Pesantren - Ahmadi Ahmadi; Baiq Risni Maripa (Indonesian Publication Center, 2023)
Reaction rate is a conceptually layered chemistry topic because students must coordinate observable phenomena, particle-level explanations, symbolic equations, graphs, and mathematical processing of experimental data. This study aimed to describe the profile and distribution of learning difficulties across six reaction-rate subtopics among Grade XI male students in an Islamic boarding-school setting. A quantitative descriptive design was employed with 82 students at Nurul Hakim Islamic Boarding School, Kediri, West Lombok. Data were collected using a 25-item achievement test covering: reaction-rate concepts and collision theory; factors affecting rate; rate laws and reaction orders; determination of order and the rate constant; graphs and energy diagrams; and applications in daily life and industry. Difficulty percentage was calculated as one minus the ratio of the mean score to the maximum score. The overall difficulty level was 45%, classified as moderate. The highest difficulty occurred in determining reaction order and the rate constant from experimental data (63%, high), followed by rate laws and reaction orders (50%, moderate). The lowest difficulty was found in basic reaction-rate concepts and collision theory (30%, low). At the individual level, 59 students (71.95%) were in the moderate-difficulty category and 23 students (28.05%) were in the low-difficulty category. These findings indicate that students' main barrier lies not in recalling basic concepts but in coordinating proportional reasoning, variable control, and symbolic calculations. Instruction should therefore prioritize scaffolded analysis of experimental tables, explicit links among macroscopic, submicroscopic, and symbolic representations, and guided practice in determining reaction orders and rate constants.